2023
DOI: 10.1101/2023.10.08.561406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relating strain amplitude, strain threshold and bone formation rate to exogenous forcing frequency

Jitendra Prasad,
Achsah Marlene Aruva,
Himanshu Shekhar
et al.

Abstract: The literature supports the existence of a strain threshold, above which cortical bone adapts to exogenous mechanical loading by forming new bone. This strain threshold, however, varies with loading conditions, locations, waveforms, frequency etc. and there is a need to mathematically express the strain threshold in terms of these parameters. There have been several parametric, mathematical or numerical models in the literature for the cortical bone’s adaptation to mechanical loading, which may be already fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 42 publications
0
1
0
6
Order By: Relevance
“…The developed disuse model showed the linear relation between MRR and the √Ø (i.e., the square root of the dissipation energy density), which is in accordance with the earlier work by Sugiyama et al (Sugiyama et al, 2012). Note that the dissipation energy density is proportional to the square of strain and, hence, MRR being proportional to √Ø is akin to bone formation rate (BFR) being proportional to the strain (Prasad, 2023). A work by Singh et al (Singh et al, 2023) has also shown a similar kind of trend, i.e., the rate of new bone formation is directly proportional to the √Ø.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The developed disuse model showed the linear relation between MRR and the √Ø (i.e., the square root of the dissipation energy density), which is in accordance with the earlier work by Sugiyama et al (Sugiyama et al, 2012). Note that the dissipation energy density is proportional to the square of strain and, hence, MRR being proportional to √Ø is akin to bone formation rate (BFR) being proportional to the strain (Prasad, 2023). A work by Singh et al (Singh et al, 2023) has also shown a similar kind of trend, i.e., the rate of new bone formation is directly proportional to the √Ø.…”
Section: Discussionmentioning
confidence: 99%
“…The axial load associated with physiological loading condition was obtained from the literature (Prasad et al 2010). In accordance with the literature, the periosteal and endocortical bone surfaces were assumed to be completely impermeable and permeable, respectively, (Singh, Singh, and Prasad 2023) (Gatti et al 2021) (Fan et al 2016) implemented through zero-flow and zero-pressure boundary conditions respectively (Fig. 2(b)).…”
Section: Methodsunclassified
See 3 more Smart Citations